Pembelajaran Bahasa Dalam Gamitan Pendidikan Karakter Dan Kurikulum Karakter - Nurazmi Br Siregar; Hamidah Sal’Aty; Nisa Amelia Purba; Harri Gusnirwanda (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This The purpose of this article is to understand how language learning in the lower grades of elementary school includes aspects of reading, writing, listening and speaking as well as to understand the importance of character education and Indonesian language learning which will be integrated in the teaching and learning process. The term learning is often heard in the study of education in schools today. This term is a development of the term "Teaching and Learning Process" (PBM). Literacy aspects are very important to be taught in the first grade of elementary school. Through reading and writing, all knowledge is absorbed by students, who can read, hear, and understand and define the meaning of words that they remember well. However, the difficulty of learning to read and write in the early stages lies in the strategies used. Learning should be a fun and meaningful activity for younger students. In other words, it is an activity that is close to the daily life of a student. Therefore, the strategies that can be applied are reading game learning strategies and early writing learning strategies using the SAS method.